Influence of Proton Irradiation on Thin Films of AZO and ITO Transparent Conductive Oxides—Simulation of Space Environment - Katarzyna Ungeheuer; Janusz Rybak; Amelia E. Bocirnea; Denis A. Pikulski; Aurelian C. Galca; Konstanty W. Marszalek (Applied Sciences)
Transparent conductive oxides are essential materials for many optoelectronic applications. For new devices for aerospace and space applications, it is crucial to know how they respond to the space environment. The most important issue in commonly used low-Earth orbits is proton radiation. This study examines the effects of high-energy proton irradiation (226.5 MeV) on thin films of aluminium-doped zinc oxide (AZO) and indium tin oxide (ITO). We use X-ray diffraction and electron microscopy observations to see the changes in the structure and microstructure of the films. The optical properties and homogeneity of the materials are determined by spectrophotometry and spectroscopic ellipsometry (SE). Analysis of the chemical states of the elements with X-ray photoelectron spectroscopy (XPS) gives insight into what proton irradiation changes at the surface of the oxides. All measurements show that ITO is less influenced than AZO. The proton energy and fluence used in this study simulate about a hundred years in low Earth orbit. This research demonstrates that both transparent conductive oxide thin films can function under simulated space conditions, with ITO showing superior resilience. The ITO film was more homogenous in terms of the total thickness measured with SE, had fewer defects and adsorbates present on the surface, as XPS analysis proved, and did not show a difference after irradiation regarding its optical properties, transmission, refractive index, or extinction coefficient.